PREDICTION OF ”RATE OF PENETRATION” (ROP) ON DRILLING FORMATION ”X” PROGNOSIS WELL ”YN2” BASED ON THE REPRESENTATIVE MODELLING FROM DRILLING FORMATION ”X’’ ACTUAL WELL ’’YN1’’ FIELD ’’IP’’ - Suhascaryo, KRT. Nur; Sudarmoyo, Sudarmoyo; Pratomo, Inrianto (Journal TECHNO, 2020)
Prediction value of the rate of penetration (ROP) in the drilling of the formation “X” well prognosis "YN2" in the field “IP” and the actual well "YN1" as a review of the selection of a representative Model-ROP at a depth of 2620 mbpl - 3000 mbpl in the "IP" field ". This study selected a representative Model-ROP from drilling the "X" formation of the actual well "YN1" in the "IP" field then predicting the rate of penetration (ROP) value in the drilling of the "X" formation of the "YN2" prognosis well in the "IP" field. ROPs used in this study include the Bingham Model (1966), Teale (2008) and Mottahari (2010). Prediction of the rate of penetration (ROP) value in the drilling of the "X" formation well "YN2" prognosis is done in stages including predicting the rate of penetration (ROP) value in the drilling of the "X" formation of the actual well "YN1" by collecting data including data on "YN1" actual well drilling includes bit records, drilling reports, well programs, and well profiles and then predicts the rate of penetration (ROP) value in the drilling of the "X" well formation "YN2" using drilling prognosis. Determine the drilling parameters needed to predict the value of the rate of penetration (ROP) has a difference in each model. In the Bingham model the parameters required include MD, WOB, RPM, T, and d-exp values. In the Teale model the required drilling parameters contain the actual MD, WOB, RPM, T, DB, and ROP values, MSE, μ and AB. In the Mottahari Model, the drilling parameters needed for MD, WOB, RPM, T, DB, actual ROP, σ, Wf (use function), G (model coefficients representing drillability), a = 0.50 and y = 1,50 is obtained from assumptions. In the Bingham Model has a coordination coefficient value (R2) = 0.9985, the Teale Model has a coordination coefficient value (R2) = 1 and the Mottahari Model has a co-coefficient value (R2) = 1. The ROP model that represents the drilling of the "X" formation Actual wells "YN1" can all be used or all Model-ROPs represent to predict the value of the penetration rate (ROP) in drilling the "X" formation prognosis of the well "YN2". Calculate the estimated penetration rate (ROP) in the drilling of the "X" formation prognosis of the well "YN2" using the Bingham, Teale and Mottahari models through the prognosis of the drilling "YN2".